2023
DOI: 10.1101/2023.11.30.569086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wind Gates Olfaction Driven Search States in Free Flight

S. David Stupski,
Floris van Breugel

Abstract: For any organism tracking a chemical cue to its source, the motion of its surrounding fluid provides crucial information for success. For both swimming and flying animals engaged in olfactory search, turning into the direction of oncoming wind or water current is often a critical first step [Marsh et al., 1978, Carton and Montgomery, 2003]. However, in nature, wind and water currents may not always provide a reliable directional cue [Crall et al., 2017, Houle and van Breugel, 2023, Carvalho and Gonçalves, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…This, in conjunction with our previously published result of a decrease in speed after plume encounters [20] suggests that the decrease in the head-pitch motion might be a strategy to localize the odor source. Interestingly, this reduction in ground speed right upon attractive odor presentation has also been recently shown in walking flies [37], and in freely flying flies upon optogenetic activation of the olfactory receptors [38].…”
Section: Discussionsupporting
confidence: 59%
“…This, in conjunction with our previously published result of a decrease in speed after plume encounters [20] suggests that the decrease in the head-pitch motion might be a strategy to localize the odor source. Interestingly, this reduction in ground speed right upon attractive odor presentation has also been recently shown in walking flies [37], and in freely flying flies upon optogenetic activation of the olfactory receptors [38].…”
Section: Discussionsupporting
confidence: 59%
“…In odor-guided navigation, temporal odor cues correlate to specific behavioral features such as moving, stopping, and turning (4, 8, 10, 11, 16, 18, 76, 77). In this work, we have shown that the frequency and duration of odor encounters are well-encoded by ORNs.…”
Section: Discussionmentioning
confidence: 99%
“…The nematode c. elegans shifts between wide-spread exploratory runs and localized dwelling in response to changes in the availability of food (Ben Arous et al, 2009; Shtonda and Avery, 2006). Similarly, both larval and adult Drosophila alter turn statistics in response to changes in odor concentration (Gomez-Marin et al 2011, Davies et al 2015, Steck et al 2013, Alvarez-Salvado et al 2018, Demir et al 2020, Stupski et al 2023). How motor and premotor circuitry are organized to regulate these statistical features of locomotion is not clear.…”
Section: Introductionmentioning
confidence: 99%